PENGARUH PARTISIPASI DALAM PENYUSUNAN ANGGARAN, KEJELASAN SASARAN ANGGARAN, STRUKTUR DESENTRALISASI, DAN SISTEM TEKNOLOGI INFORMASI TERHADAP KINERJA MANAJERIAL PEMERINTAH DAERAH (STUDI KASUS PADA PEMERINTAH DAERAH PROVINSI RIAU - ', Mila Suhardini; ', Kamaliah '; ', M.Rasuli ' (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
This study aims to test the Influence of Participation in Budgeting, Budget Goal Clarity, Structure Decentralization, and the Information Technology Systems Managerial Performance Local Government (Case Studies on Local Government of Riau Province). The sampling method using purposive sampling technique, the choice of non-probability samples that meet certain considerations. The author conducted research based data retrieval techniques through questionnaires. Analysis of the data used has properties quantitative analysis of data through multiple linear regression equation with the t test and the partial test R2 and collected data is processed with the statistical program SPSS 17.0. The results were obtained as a partial conclusion that four variables t (5,665, 9,482, 3,906 and 7,174) with four variables indicate t is greater than t table. It was concluded that the four variables (Participation in Budgeting, Budget Goal Clarity, Structure Decentralization, and Information Technology Systems) in this study a significant effect on Managerial Performance of Local Government. Moreover, judging from the determination of a test in which the values of R 0,934 and adjusted R2 0,867 or 86,7%. independent variables affect the dependent variable, is13,3% influenced by other variables.Kata Kunci : Budget, decentralization, technology and performance